Penggunaan Sonkeigo Dan Kenjougo Dalam Drama Ouroboros: Kono Ai Koso Seigi - Fadhilatul Annisa; Maulluddul Haq (Universitas Negeri Padang, 2023)
Sonkeigo and kenjougo are types of respectful language (keigo). This study aimed at describing the various forms of sonkeigo and kenjougo in Drama Ouroboros: Kono Ai Koso Seigi. Indicators of the types sonkeigo and kenjougo is based on the theory of Sudjianto and Dahidi. This study was a qualitative research with uses a qualitative descriptive approach. The data in this study using sentences that containing sonkeigo and kenjougo and the data source was a drama Ouroboros: Kono Ai Koso, Seigi. Data collection using the method of simak bebas libat cakap (SBLC) and notes. In data analysis using the Miles and Huberman models; data reduction, data display, and verification/conclusions. The result of this study were; 54 words of sonkeigo and 47 words of kenjougo.